Anticrack nucleation as triggering mechanism for snow slab avalanches - Heierli, Joachim; Zaiser, Michael; Gumbsch, Peter (Science, 2008)
Snow slab avalanches are believed to begin by the gravity- driven shear failure of weak layers in stratified snow. The critical crack length for shear crack propagation along such layers should increase without bound as the slope decreases. However, recent experiments show that the critical length of artificially introduced cracks remains constant or, if anything, slightly decreases with decreasing slope. This surprising observation can be understood in terms of volumetric collapse of the weak layer during failure, resulting in the formation and propagation of mixed- mode anticracks, which are driven simultaneously by slope- parallel and slope- normal components of gravity. Such fractures may propagate even if crack- face friction impedes downhill sliding of the snowpack, indicating a scenario in which two separate conditions have to be met for slab avalanche release.